Investigation of the Characteristics of a Photodetector with a High Photocurrent when Transmitting Microwave Radio Signals Through an Optical Fiber - I. Yu. Tatsenko; T. K. Legkova; A. V. Ivanov; A. B. Ustinov (Известия высших учебных заведений России: Радиоэлектроника, 2020)
Introduction. At present, an optical transmission of a microwave signal is of great scientific and practical interest. Moreover, this transmission line can also be used to create microwave photonic devices. Microwave signal losses decrease with an increase of laser power. Commercial photodetectors withstand radiation with a power of several tens of milliwatts. Using a photodetector with a high photocurrent can improve characteristics of photonic transmission lines; in particular, it can reduce microwave signal losses.Aim. Investigation of characteristics of a photodetector with a high photocurrent when transmitting microwave radio signals through optical fiber. Research of microwave signal losses as a function of optical power.Materials and Methods. Experimental studies were carried out on created experimental schemes for studying the characteristics of the photodetector with modulated and unmodulated optical radiation. Theoretical studies were carried out by mathematical modeling of optical path transfer characteristics from the laser power at various powers of an input microwave signal.Results. The dependencies of photocurrent and photovoltage of the photodetector versus laser power were obtained. The experimental amplitude-frequency characteristics of the photonic transmission line were measured at different optical powers. A frequency dependence of the photodetector sensitivity in the range of 0...12 GHz was obtained. Modeling of amplitude-frequency characteristics of the optical path in the range of 0...12 GHz was performed. An approximate frequency dependence of the photodetector sensitivity was obtained.Conclusion. Due to the use of a photodetector with a high photocurrent value and with increasing laser power, microwave losses were reduced to about 10 dB. It was shown that for improving the transmission characteristics of an optical transmission line, it is necessary to use a broadband electro-optical modulator.